Ten Years after Sutton (2012): Quo Vadis Feedback Literacy? (A Bibliometric Study) - Gozali, Imelda; Syahid, Abdul; Suryati, Nunung (Register Journal, 2023)
Drawing on the construct of Academic Literacy, Paul Sutton coined the term "Feedback Literacy" in 2012. Since then, a growing body of research on Feedback Literacy has emerged from scholars worldwide. This bibliometric study then intended to trace the historical development of Feedback Literacy research over a decade and identify future trends and directions in the field. Extracting from the Scopus database and employing Bibliometrix R-tool, this study seeks to reveal the performance analysis and science mapping of the construct. PRISMA 2020 was utilized to guide the articles' search, screening, selection, and reporting. The result of the performance analysis revealed the most prominent journal (Assessment and Evaluation in Higher Education), author (David Carless), article (Carless & Boud, 2018), and keywords (students-related feedback) in feedback literacy research. The conceptual, intellectual, and social structure analyses under science mapping provided insight into popular and fundamental research themes and the collaboration network among feedback literacy authors, with Australian researchers at the forefront. The findings imply that feedback literacy is a fertile ground for further research on topics such as students-related feedback, online feedback, ecological factor, and dialogic feedback. Studies outside of the context of higher education are still under-represented. This study can also aid novice scholars m finding relevant references or outlets for publication.